Respuesta :

Answer:

[tex]y=-0.667x+-10[/tex]

Step-by-step explanation:

Given the following question:

Point A = (-9, -4), (x1, y1)
Point B = (-6, -6), (x2, y2)

[tex]m=\frac{y2-y1}{x2-x1}[/tex]
[tex]m=\frac{-6--4}{-6--9} =\frac{-2}{3}[/tex]
[tex]m=\frac{-2}{3}[/tex]

Write in slope intercept form:

[tex]y=mx+b[/tex]
[tex]m=\frac{-2}{3}=-2\div3=-0.667[/tex]
[tex]y=-4[/tex]
[tex]x=-9[/tex]
[tex]-4=-0.667\times-9+b[/tex]
[tex]-0.667\times-9=6[/tex]
[tex]b=-10[/tex]
[tex]y=-0.667x+-10[/tex]

Hope this helps.